Factors Related To The Utilization Of Integrated Development Posts Non-Communicable Disease In Lekogoko Village Working Area Of Aimere Public Health Center - Yohana Bhoki; Erny Erawati Pua Upa; Dominirsep O. Dodo (Universitas Nusa Cendana, 2022)
The Non-Communicable Disease Posbindu Program is one of the government's action plans for overcoming non-communicable diseases. Aimere Puskesmas is the Puskesmas with the highest number of Posbindu, namely 11 Posbindu. This study aims to determine the factors associated with the utilization of Posbindu Non-Communicable Diseases in Lekogoko Village, the work area of ​​Aimere Public Health Center in 2020. The research approach used was an analytical survey with a cross-sectional design. The sample used amounted to 157 people with the sampling technique using proportional stratified random. Data analysis used univariate analysis and bivariate analysis. The results of statistical tests using chi-square analysis showed that there was a relationship between knowledge (p = 0.003), motivation (p = 0.001) distance from home (0.009), support from cadres (0.000), and family support (0.009) with the use of Posbindu Non-Communicable Diseases. This study concludes that there is a relationship between knowledge, support from health cadres, and family support with the use of Posbindu Non-Communicable Diseases. It is recommended to carry out monitoring and evaluation from local health workers in terms of increasing knowledge and skills for cadres, especially related to effective communication in inviting people to be active in regularly checking their health at Posbindu Non-Communicable Diseases.